OPTIMALISASI SOSIAL MEDIA DALAM MENINGKATKAN PENGEMBANGAN BRANDING LEMBAGA SEKOLAH LABORATORIUM UNPATTI - Hadi, Hafid Kholidi; Vicky Dwi Wicaksono; Mas Suryanto, H.S; Andhega Wijaya; Achmad Kautsar (Universitas Negeri Surabaya, 2025)
Social media has a function in conveying information quickly and flexibly. SMA Laboratorium UNPATTI is expected to utilize social media to develop the learning process at SMA Laboratorium UNPATTI. To overcome partner problems, by providing training on optimizing social media in teacher development at SMA Laboratorium UNPATTI, it is expected to be able to increase knowledge and improve teacher professionalism. The method of this community service activity starts from the field survey stage, preparation, to implementation. The survey stage is carried out with school partners to identify obstacles, needs, and opportunities faced. The output of this community service is an understanding of the importance of social media in school branding. The level of acceptance of teacher technology towards social media through a questionnaire is 85% understanding the importance of social media, and 95% understanding the benefits of social media for professional development. As many as 80% of participants have never received social media marketing training before and 95% showed sufficient interest in taking part in training on social media.